Liquid Spheres on Smartphones: The Personal Information Policies - Serrano Tellería, Ana; Oliveira, Marco (International Journal of Interactive Mobile Technologies (iJIM), 2015)
Data collected from the profiles and the digital identities has become a valuable currency for the mobile ecosystem, especially between users and providers. Services that required them are also described as the ground floor in direct linked with the infrastructures and as intermediate layers between networks, platforms and applications. The frontier debate between innovation and protection of privacy is shown off undefined and unstable. Therefore, a comparative analysis between ‘Privacy Terms and Conditions’ as well as the interrelation between operative systems (Apple iOS, Android, Blackberry and Windows Phone), social media platforms (Facebook, LinkedIn, Twitter and Google +) and applications (Instagram, WhatsApp, Line and Vine) have been carried out focusing on Privacy issues. Two main tendencies were appreciated in relation with the two principal operative systems: Apple iOS closed environment and Google Android open source. They reconfigure the functional structure and design of platforms and applications in different ways. The liquid spheres observed varied from the first approach that tried to control every action and personal information from the binomial operative system-device and the second one that allowed the user actions and information to be more susceptible to interact with any kind of applications and platforms while the system is linked to information aggregation services to collect the data. Prominent aspects were the various stages of synchronization between the different levels of personal information (contacts, profile, digital identity and localization). Focusing on the case of Portugal, other complementary conclusions obtained from focus group and surveys showed a strong circumstantial pattern behaviour and a concern about privacy issues taking care of some actions while admitted checking if they had the terms and conditions involved - which are too ambiguous - but not reading them. Described also by other international previous researches, they showed lack of rationality in some attitudes and performances and limitations on the extension between knowledge and action.